2014
DOI: 10.1590/s0100-06832014000200028
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição das fontes de sedimentos em uma bacia hidrográfica agrícola sob plantio direto

Abstract: O conhecimento das principais fontes difusas de produção de sedimento pode aumentar a eficiência de utilização dos recursos públicos, investidos em estratégias de gestão em bacias hidrográficas, que visem mitigar a transferência de sedimentos aos cursos d'água. Objetivou-se com este trabalho avaliar as fontes de sedimentos numa bacia hidrográfica rural de cabeceira com predomínio de cultivos anuais sob plantio direto e com intensa e inadequada exploração dos recursos naturais, por meio da quantificação da cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
0
18
0
5
Order By: Relevance
“…Rural road networks may provide a continuous sediment source to rivers during the entire year in wet tropical regions (Thomaz, Vestena, & Ramos Scharrón, ). Sediment fingerprinting studies conducted in small rural catchments from Southern Brazil where soils are frequently plowed showed that unpaved roads contribute on average 25−50% of suspended sediments (Minella et al, ; Tiecher et al, ; Tiecher et al, ; Tiecher et al, ). However, according to Didoné et al (), the values obtained in these small catchments (<1.5 km 2 ) might not necessarily be extrapolated to larger catchments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rural road networks may provide a continuous sediment source to rivers during the entire year in wet tropical regions (Thomaz, Vestena, & Ramos Scharrón, ). Sediment fingerprinting studies conducted in small rural catchments from Southern Brazil where soils are frequently plowed showed that unpaved roads contribute on average 25−50% of suspended sediments (Minella et al, ; Tiecher et al, ; Tiecher et al, ; Tiecher et al, ). However, according to Didoné et al (), the values obtained in these small catchments (<1.5 km 2 ) might not necessarily be extrapolated to larger catchments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to modeling and monitoring studies, the sediment fingerprinting technique was shown to provide a powerful tool to identify sediment sources in Brazil (Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ; Minella, Merten, Reichert, & dos Santos, ; Minella, Merten, Walling, & Reichert, ; Minella, Walling, & Merten, , ; Tiecher et al, ; Tiecher, Caner, et al, ; Tiecher, Caner, Minella, & dos Santos, ; Tiecher, Caner, Minella, Bender, & dos Santos, ; Tiecher, Minella, et al, ) and elsewhere in the world, such as in France (Foucher et al, ; Legout et al, ; Navratil, Evrard, Esteves, Legout, et al, ; Poulenard et al, ), Mexico (Evrard et al, ), South Africa (Foster, Boardman, & Keay‐Bright, ), Zambia (Walling, Collins, Sichingabula, & GJL, ), Canada (Barthod et al, ; Koiter et al, ; Stone, Collins, Silins, Emelko, & Zhang, ), United States (Devereux, Prestegaard, Needelman, & Gellis, ), United Kingdom (Collins, Walling, Webb, & King, ; Pulley, Foster, & Antunes, ; Smith & Blake, ), Spain (Brosinsky, Foerster, Segl, & Kaufmann, ), Luxemburg (Martínez‐Carreras et al, ), Turkey (D'Haen et al, ), Tunisia (Ben Slimane et al, ), Iran (Haddadchi, Nosrati, & Ahmadi, ), and Australia (Laceby, McMahon, Evrard, & Olley, ; Olley, Burton, Smolders, Pantus, & Pietsch, ; Wilkinson, Hancock, Bartley, Hawdon, & Keen, ). Therefore, the objective of the current study is to quantify the contribution of sources supplying sediment to the river in a catchment characterized by the widespread implementation of NT since the 1990s in Southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Contribution of sediment‐producing sources to total sediment yield has been investigated predominantly in agricultural watersheds (Nagle & Ritchie, ; Smith, Evrard, Blake, & Owens, ) with evidence of erosion and sediment deposition (Minella, Merten, & Clarke, ; Minella, Merten, Reichert, & Santos, ; Minella, Merten, Walling, & Reichert, ; Minella, Walling, & Merten, ; Tiecher, Caner, Minella, & Santos, ; Tiecher et al, ); deforestation to prepare land for agriculture production (Bai, Zhang, Long, Liu, & Siyu, ); and in forest areas harvested and prepared for new planting (Schuller et al, ). However, information about sediment‐producing sources is incipient in areas of forestry production along the cultivation cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in watersheds under agricultural production, using fingerprinting technique for source identification of sediment transported in suspension, have been conducted successfully in several countries and have been expanding rapidly (Slimane et al, ; Smith et al, ). Studies were carried out in small rural watersheds in Southern Brazil, in sloping areas cropped mainly with tobacco in small family‐farm units (Minella et al, ; Minella et al, ; Minella, Merten, & Clarke, ; Minella, Merten, Walling, et al, ; Tiecher, Caner, Minella, Bender, et al, ; Tiecher, Caner, Minella, & Santos, ), for no‐till annual crops (Tiecher et al, ), on hillsides with shallow soils and non‐intensive agriculture (Miguel, Dalmolin, Pedron, & Moura‐Bueno, ; Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ), and for urban watersheds (Franz, Makeschin, Wei, & Lorz, ; Poleto, Merten, & Minella, ). For all these agricultural watersheds (Miguel, Dalmolin, Pedron, Moura‐Bueno, et al, ; Minella et al, ; Minella et al, ; Minella, Merten, & Clarke, ; Minella, Merten, Walling, et al, ; Tiecher et al, ), fingerprinting indicated crops and roads as main suspended sediment sources.…”
Section: Introductionmentioning
confidence: 99%
“…These fields are in steeply sloped areas, resulting in a large amount of sediment (Pellegrini et al, 2010;Bonumá et al, 2012;Bonumá et al, 2014;Tiecher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%